2003
DOI: 10.1001/jama.289.22.2963
|View full text |Cite
|
Sign up to set email alerts
|

Computer Use and Carpal Tunnel Syndrome

Abstract: Context Computer use is increasingly common among many working populations, and concern exists about possible adverse effects of computer use, such as carpal tunnel syndrome (CTS).Objectives To estimate the prevalence and incidence of possible CTS and to evaluate the contribution of use of mouse devices and keyboards to the risk of possible CTS.Design and Setting A 1-year follow-up study with questionnaires conducted in 2000 and 2001 at 3500 workplaces in Denmark, followed on each of the 2 occasions by a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(150 citation statements)
references
References 15 publications
5
140
1
4
Order By: Relevance
“…A study by Murata et al [19] has found a reduced sensory nerve conduction velocity in the median nerve across the carpal tunnel among neurologically symptomatic computer operators compared with healthy controls, indicating that a subclinical CTS was associated with computer use. However, other authors have reported that computer use had no influence on CTS occurrence [20,21].…”
Section: Study Of Nerve Conduction In Computer Users O R I G I N a L mentioning
confidence: 84%
“…A study by Murata et al [19] has found a reduced sensory nerve conduction velocity in the median nerve across the carpal tunnel among neurologically symptomatic computer operators compared with healthy controls, indicating that a subclinical CTS was associated with computer use. However, other authors have reported that computer use had no influence on CTS occurrence [20,21].…”
Section: Study Of Nerve Conduction In Computer Users O R I G I N a L mentioning
confidence: 84%
“…However, Atroshi, Gummesson, Johnsson, et al reported that the prevalence of CTS which was clinically and electrophysiologically confirmed in the general population was estimated at 2.7% [21]. In a one-year follow-up study of computer users in Denmark, the prevalence of interview-confirmed median nerve symptoms was 4.8% and the one-year incidence of new or worsened CTS symptoms was 1.4% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has focused on weekly self-reported estimates of computer use whereas we examined estimates of computer use throughout the day, along with estimates of break frequency and length captured throughout the day [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%